2011
DOI: 10.1111/j.1365-2893.2011.01490.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural prevalence of HCV minority variants that are highly resistant to NS3/4A protease inhibitors

Abstract: Minority drug-resistant hepatitis C virus (HCV) variants may go undetected yet be clinically important. NS3/4A protease resistance substitutions V36A and A156S/T/V were selected in patients treated with protease inhibitors. The aim of this study was to investigate whether these substitutions pre-existed in HCV infected patients. An allele-specific PCR protocol that detected the NS3/4A protease resistance substitutions V36A and A156S/T/V was used to determine the prevalence of naturally occurring variants in 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…One of the most important shortcomings of MAMA PCR is the fact that multiple mutations occurring in the same viral variant cannot be identified. While the detection capabilities of MAMA PCR, as well as its quantitative properties when the method is properly adapted (10,18), are unquestionable, the unfeasibility of differentiation of combinatory and single mutations taking place within the same molecule is a major drawback. Thus, usage of more advanced technology such as amplicon deep sequencing is more appropriate for a thorough evaluation of the viral population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most important shortcomings of MAMA PCR is the fact that multiple mutations occurring in the same viral variant cannot be identified. While the detection capabilities of MAMA PCR, as well as its quantitative properties when the method is properly adapted (10,18), are unquestionable, the unfeasibility of differentiation of combinatory and single mutations taking place within the same molecule is a major drawback. Thus, usage of more advanced technology such as amplicon deep sequencing is more appropriate for a thorough evaluation of the viral population.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the simplicity of MAMA PCR makes it superior to other methodologies known to be time-consuming, cumbersome, and costly. Thus, MAMA PCR is a viable alternative for HCV mutant detection (10). One of the most important shortcomings of MAMA PCR is the fact that multiple mutations occurring in the same viral variant cannot be identified.…”
Section: Discussionmentioning
confidence: 99%
“…This results in the remarkable sequence variation of an infecting HCV population, also known as a quasispecies. Among the members of an HCV quasispecies, drug-resistant mutants are likely to be present and to be able to spread between individuals (6,7). Furthermore, the current treatments are extremely expensive and thus present a significant burden for health care systems (8).…”
mentioning
confidence: 99%
“…The similarities between HIV-1 and HCV proteases found here show that it is likely that similar to HIV-1, drug-resistant mutants will preexist therapy. Indeed, we and others have shown that this is the case for NS3 protease inhibitors (18,48; reviewed in reference 49). Therefore, further work should include the study of other virus enzymes and proteins to evaluate whether the findings shown here can be extended to other virus genomic regions.…”
Section: Discussionmentioning
confidence: 99%